(untitled) (Physical Education, Health and Social Sciences, 2026)
Apple scab, caused by the hemibiotrophic ascomycete Venturia inaequalis, remains the most economically destructive disease of apple worldwide, despite more than a century of intensive research and management efforts. The pathogen’s polycyclic life cycle, combined with strong selection pressure from frequent fungicide applications and genetically uniform host cultivars, has driven rapid evolutionary adaptation, resulting in widespread fungicide resistance and repeated breakdowns of host resistance. This review synthesizes recent advances in V. inaequalis biology, fungicide resistance mechanisms, and integrated disease management strategies. Genomic and transcriptomic studies reveal a “two-speed” genome architecture enriched in transposable elements, which accelerates effector diversification and underpins the rapid erosion of monogenic resistance, exemplified by the global failure of the widely deployed Rvi6 (Vf) gene. Concurrently, extensive resistance to major fungicide classes including qualitative resistance to QoI fungicides via the cytb G143A mutation and quantitative resistance to DMIs mediated by CYP51 mutations and overexpression has culminated in stable multi-fungicide resistant populations with minimal fitness penalties. These developments severely constrain chemical control options. The review highlights that sustainable apple scab management requires a paradigm shift toward integrated strategies that reduce selection pressure and enhance durability. Key approaches include rigorous cultural practices to suppress primary inoculum, precision fungicide use guided by decision support systems capable of reducing chemical inputs by up to 80%, and the deployment of durable host resistance through gene pyramiding supported by molecular breeding and cisgenic technologies. Ultimately, the long-term viability of apple production depends on the integration of pathogen genomics, resistance stewardship, precision epidemiology, and advanced breeding to outpace the adaptive capacity of V. inaequalis.